ESBies: safety in the tranches. (6th April 2017) - Brunnermeier, Markus K; Langfield, Sam; Pagano, Marco; Reis, Ricardo; Van Nieuwerburgh, Stijn; Vayanos, Dimitri
SUMMARY: The euro crisis was fuelled by the diabolic loop between sovereign risk and bank risk, coupled with cross-border flight-to-safety capital flows. European Safe Bonds (ESBies), a euro area-wide safe asset without joint liability, would help to resolve these problems. We make three contributions. First, numerical simulations show that ESBies with a subordination level of 30% would be as safe as German bunds and would increase safe asset supply. Second, a model shows how, when and why the two features of ESBies – diversification and seniority – can weaken the diabolic loop and its diffusion across countries. Third, we propose how to create ESBies, starting with limited issuance by public or private-sector entities.